Advances in artificial muscles: A brief literature and patent review - Jing, Yuan; Su, Fangfang; Yu, Xiaona; Fang, Hui; Wan, Yuehua (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Artificial muscles are an active research area now. Methods: A bibliometric analysis was performed to evaluate the development of artificial muscles based on research papers and patents. A detailed overview of artificial muscles' scientific and technological innovation was presented from aspects of productive countries/regions, institutions, journals, researchers, highly cited papers, and emerging topics. Results: 1,743 papers and 1,925 patents were identified after retrieval in Science Citation Index-Expanded (SCI-E) and Derwent Innovations Index (DII). The results show that China, the USA, and Japan are leading in the scientific and technological innovation of artificial muscles. The University of Wollongong has the most publications and Spinks is the most productive author in artificial muscle research. Smart Materials and Structures is the journal most productive in this field. Materials science, mechanical and automation, and robotics are the three fields related to artificial muscles most. Types of artificial muscles like pneumatic artificial muscles (PAMs) and dielectric elastomer actuator (DEA) are maturing. Shape memory alloy (SMA), carbon nanotubes (CNTs), graphene, and other novel materials have shown promising applications in this field. Conclusions: Along with the development of new materials and processes, researchers are paying more attention to the performance improvement and cost reduction of artificial